Analysis of canine dimorphism in the estimation of sex - Yuri Trigueiro Faustino da Costa; Laíse Nascimento Correia Lima; Patrícia Moreira Rabello (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the sexual dimorphism of mandibular and maxillary canines among dental students of the Federal University of Paraiba, Brazil. Methods: This was an observational, blind and cross-sectional study with comparative and statistical-descriptive procedure. Fifty-one pairs of plaster models belonging to undergraduate dental students aged 18-29 years were analyzed. Quantitative data were organized and processed by means of the Statistical Package for the Social Sciences (SPSS) software, version 15.0. This research has followed the guidelines of 196/ 96 Brazilian Resolution of the National Health Council, Ministry of Health. Results: All measures were found to show statistically significant differences between sexes (p<0.001) according to Student's t-test. Regarding the difference between the four canines for each sex separately, it was found difference only between mandibular and maxillary canines (p<0.001) according to the F test (ANOVA), but with no significant difference between the right and left sides. Conclusions: Odontometric techniques allowed concluding that canine teeth present statistically significant sexual dimorphism, and that they may be useful in the estimation of sex in complementary methods during body identification. The data obtained in this study were compared with those of other studies to provide information about sexual dimorphism be specific for each population.